Rational Boreholes Arrangement of Gas Extraction from Unloaded Coal Seam - Chaojun Fan; Sheng Li; Haohao Zhang; Zhenhua Yang (Advances in Civil Engineering)
In order to enhance gas extraction from unloaded coal seam by drilling borehole in the floor roadway, the mechanism of stress relief improving permeability by protective coal seam mining was analyzed. Based on the multiphysics field theory, the hydraulic-mechanical coupling model of gas extraction in the unloading coal seam was established, and the gas extraction process by drilling borehole in the floor roadway in the overburden of Panyi Coal Mine 1551 (1) panel was simulated. The influence of different drilling arrangements on the gas extraction effect was analyzed. The results show that the permeability of protected coal seams is characterized by zoning and can be divided into the permeability-enhanced zone, the permeability-reduced zone, and the original permeability zone according to the stress state of coal seam. Under the condition of uniform borehole distribution, the gas pressure decreased slowly in the permeability-reduced zone and is still greater than 0.74 MPa after 180 days of extraction, and there is a large extraction blind area in the protected panel. Under the condition of nonuniform borehole distribution arrangement according to the characteristics of permeability zoning, the effective extraction area can almost cover the protected panel, and the blind extraction area is reduced by 91.22% when compared to uniform borehole distribution. These can provide a reference for unloading gas extraction under similar conditions.